The Early Evolution of Spinal Cord Lesions on MR Imaging following Traumatic Spinal Cord Injury - Leypold, B.G.; Flanders, A.E.; Burns, A.S. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: How early spinal cord injury (SCI) lesions evolve in patients after injury is unknown. The purpose of this study was to characterize the early evolution of spinal cord edema and hemorrhage on MR imaging after acute traumatic SCI.MATERIALS AND METHODS: We performed a retrospective analysis of 48 patients with clinically complete cervical spine injury. Inclusion criteria were the clear documentation of the time of injury and MR imaging before surgical intervention within 72 hours of injury. The length of intramedullary spinal cord edema and hemorrhage was assessed. The correlation between time to imaging and lesion size was determined by multiple regression analysis. Short-interval follow-up MR imaging was also available for a few patients (n = 5), which allowed the direct visualization of changes in spinal cord edema.RESULTS: MR imaging demonstrated cord edema in 100% of patients and cord hemorrhage in 67% of patients. The mean longitudinal length of cord edema was 10.3 ± 4.0 U, and the mean length of cord hemorrhage was 2.6 ± 2.0 U. Increased time to MR imaging correlated to increased spinal cord edema length (P = .002), even after accounting for the influence of other variables. A difference in time to MR imaging of 1.2 days corresponded to an average increase in cord edema by 1 full vertebral level. Hemorrhage length was not affected by time to imaging (P = .825). A temporal increase in the length of spinal cord edema was confirmed in patients with short-interval follow-up MR imaging (P = .003).CONCLUSION: Spinal cord edema increases significantly during the early time period after injury, whereas intramedullary hemorrhage is comparatively static.